O Plano de Desenvolvimento Institucional como ferramenta de planejamento e gestão universitária - Balisa, Alyne Ferreira Costa (2020)
The objective of this research is to understand the use of the Institutional Development Plan (PDI) as an instrument of university strategic management. It is a qualitative and exploratory research carried out through bibliographic and documentary research. Data analysis was based on the contextual approach and used the triangle of changes proposed by Pettigrew (1987). As a result of this research, it shows the existing gap between the content proposed by the institutions' PDI and the absence or insufficiency of the approach on the criteria evaluated by the General Course Index (IGC). This, in a way, denotes the non-observance by the managers of the fundamental criteria for improving the quality of the courses, although the 5 (five) universities best classified in the ranking have also been analyzed. The fact is that the PDI, in many cases, is seen as a mandatory element built with the purpose of complying with legal requirements, that is, it is little configured as a document to support university management in terms of improving institutional development indicators, especially for the evaluation of higher education courses. It should be noted, however, that the completeness of the environmental analysis is preponderant in the preparation of university planning (GOHR; SANTOS, 2011; PEREIRA; COELHO, 2018; PEREIRA, 2019) and, therefore, it is recommended that university managers guide if for the analysis of the relationship between content, context and process (what to do, why it needs to be done and how to proceed / conduct), adopting criteria and technical parameters in the choices, in order to minimize the political impact of decisions and enhance the organizational results , directing actions to improve the indicators used by INEP and other international rankings. Finally, it would be worth checking, in future research, if it would be possible to improve the quality of the courses even more if the IGC criteria were better worked out in the specification of actions and projects.